Radiotherapy in Oligometastatic, Oligorecurrent and Oligoprogressive Prostate Cancer: A Mini-Review - Yaney, Alexander; Stevens, Andrew; Monk, Paul; Martin, Douglas; Diaz, Dayssy A.; Wang, Shang-Jui (Frontiers in Oncology, 2022)
Globally, prostate cancer is one of the most common malignancies affecting men. With the advent of advanced molecular imaging, an increasing number of men are found to have oligometastatic disease (OD) either at primary diagnosis or at the time of biochemical failure. No strict definition exists for OD, with historical and ongoing studies utilizing diverse criteria. There is mounting evidence from many different malignancies that patients with OD have improved outcomes compared to their widely metastatic counterparts. As such, treatment intensification of those with OD or oligoprogressive disease has become an area of intense interest and study. This article will review the biology, evidence and controversy behind the treatment of de novo oligometastatic, oligorecurrent and oligoprogressive prostate cancer.